2023
DOI: 10.1097/ju.0000000000003611
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Bladder Management, Symptoms, and Satisfaction After Spinal Cord Injury

Abstract: Purpose: We sought to characterize sex-stratified differences in bladder management and bladder symptoms and satisfaction after spinal cord injury. Materials and Methods: This study was a prospective, cross-sectional, observational study; eligibility included: age !18 years and acquired spinal cord injury. Bladder management was grouped as (1) clean intermittent catheterization, (2) indwelling catheter, (3) surgery, and (4) voiding. Primary outcome was Neurogenic Bladder Symptom Score. Secondary outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Future studies will need to be completed in both male and female rats to compare potential sex differences in ampakine effects. While we have not observed any sex effects of ampakines in our respiratory studies ( Rana et al, 2021 ), there are known differences in recovery and injury manifestation between male and females that need to be further studied ( Anderson et al, 2023 ; Myers et al, 2023 ).…”
Section: Discussionmentioning
confidence: 62%
“…Future studies will need to be completed in both male and female rats to compare potential sex differences in ampakine effects. While we have not observed any sex effects of ampakines in our respiratory studies ( Rana et al, 2021 ), there are known differences in recovery and injury manifestation between male and females that need to be further studied ( Anderson et al, 2023 ; Myers et al, 2023 ).…”
Section: Discussionmentioning
confidence: 62%
“…In the NBRG registry, we have shown that women are less likely to use intermittent catheters, and more likely to undergo NLUTD-related surgery; in multivariable regression female sex was associated with worse symptoms and lower QOL. 5,20 A cross-sectional study of 135 women with SCI found they had worse NLUTD symptoms than men, and their QOL was dependent on bladder management. 21 The female predominant cluster in the current study serves to both confirm these previous findings using a different analytic technique, and also to demonstrate that while female sex is likely a significant risk factor for urinary symptoms and poor QOL after SCI, it has complex interactions with other variables as women were also present (making up 33%) in the high functioning, low complications cluster.…”
Section: Discussionmentioning
confidence: 99%
“…In the accompanying article, Myers and colleagues describe important gender-specific experiences of patients with spinal cord injury (SCI) managed at tertiary urology centers. 1 The Neurogenic Bladder Symptom Score (NBSS) was administered to all patients upon entry and served as the primary outcome measure for the multicenter study. Interestingly, at entry, women had significantly higher NBSS scores, more self-reported urinary tract infections, and were much more likely to have undergone surgical intervention (catheterizable channel AE augmentation).…”
Section: Editorial Commentmentioning
confidence: 99%